PENGARUH LIKUIDITAS, PERTUMBUHAN PENJUALAN, PERPUTARAN MODAL KERJA, DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Afrilenny Marista BR Hombing, 15.05.52.0341; Parmono Hadi, Teguh (Students' Journal of Accounting and Banking, 2019)
This study aimed to determine and analyze the effect of liquidity, sales growth, working capital turnover, and leverage on profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The type of data used in this study was secondary data. Data from this report were obtained from the 2015-2017 Annual Report (AR). This research was conducted using a sample of 184 manufacturing companies listed on the Stock Exchange in 2015-2017. The sample selection method used purposive sampling and the analysis model used was multiple linear regression. The results of this study indicated that liquidity had a positive and significant effect on profitability, sales growth had no effect on profitability, working capital turnover had no effect on profitability, and leverage had no effect on profitability.